Correlates of post-COVID-19 pandemic worry and preventive practices in older adults in Florida - Mirza M. Baig; Lilah M. Besser; Magdalena I. Tolea; Michael J. Kleiman; Lun-Ching Chang; Deirdre M. O’Shea; Stephanie Chrisphonte; Lisa K. Wiese; James E. Galvin (Frontiers in Public Health, 2025)
IntroductionThe extant literature is limited regarding the correlates of COVID-19 worry and preventive measures among diverse, older adults following the peak of the pandemic. Purpose of the study is to determine the correlates of post-COVID-19 pandemic worry and preventive practices (i.e., social distancing, masking) among older adults.Materials and methodsIn 2022–2024, we conducted a cross-sectional survey of COVID-19 preventive behaviors, concerns, beliefs, and trusted sources of information in older adults in rural and urban/suburban settings in south-central Florida. A convenience sample of 522 English-speaking participants age 60 years or older were recruited using word-of-mouth, flyers, and recruitment events in urban, suburban, and rural settings. Comparisons were made for COVID-19 worry and preventive practices across key sociodemographic variables (e.g., age, sex, race/ethnicity, education, vaccination status, residence, and COVID-19 testing history) using multivariable linear and logistic regression models.ResultsParticipants (mean age 72 ± 9 years) were predominantly women (73%), Black (74%), and rural residents (57%). Greater COVID-19 worry was higher among participants who were younger, women, less educated, vaccinated, rural residents, never testing positive for COVID-19, and trusted authorities for health information. Black and Hispanic participants, as well as vaccinated individuals, were more likely to mask in public, while women and Black and Hispanic participants were more likely to practice social distancing.DiscussionPost-COVID-19 pandemic worry and preventive practices were correlated with demographics, vaccination status, and trust in health authorities. The findings underscore the importance of targeted public health messaging and interventions that consider the distinct needs and concerns of diverse older adult populations. This study’s explicit focus on sociodemographic differences provides valuable insights for designing more effective pandemic preparedness and response strategies tailored to vulnerable and diverse communities.